Valuing height: diagnosis, valuation and the case of idiopathic short stature - Morrison, M (John Wiley and Sons, Ltd., 2018)
This paper proposes a ‘valuographic’ approach to diagnosis, exploring how values and valuation practices are implicated in the contested diagnostic category of idiopathic short stature (ISS). ISS describes children who are ‘abnormally’ short but do not have any other detectable pathology. In the USA growth‐promoting hormone therapy has been approved for ISS children, since 2003. However, no other jurisdiction has approved this treatment and the value of ISS as a diagnostic category remains disputed among healthcare professionals. Drawing on qualitative interviews with paediatric endocrinologists in the UK and the US, this study presents a historical snapshot illustrating how the problematisation of ISS as a diagnosis involved multiple registers of value including epistemic, economic and moral calculations of worth. Contestation of the diagnosis was not just about what counts but about what ought to be counted, as respondents’ accounts of ISS gave differential weight to a range of types of evidence and methods of assessment. Ultimately what was at stake was not just the value of increased height for short patients, but what it meant to properly practice paediatric endocrinology. Consideration is then given to how a valuographic approach can be applied to sociological studies of diagnosis more broadly.